2022
DOI: 10.11604/pamj.2022.41.75.28488
|View full text |Cite
|
Sign up to set email alerts
|

A structural equation model to explore sociodemographic, macroeconomic, and health factors affecting life expectancy in Oman

Abstract: Introduction the factors determining life expectancy (LE) are crucial for policymakers to study in implementing an effective and accurate intervention in society. In Oman, the available data over the past four decades were not extracted to develop a statistical model to understand how the sociodemographic (SD), macroeconomic (ME), and health-status and resources (HSR) factors affecting LE. The study was aimed at creating a representative model to explain the factors affecting LE in Oman and examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The theoretical model proposed for this study was based on a conceptual framework from previous studies in ASEAN countries 35–37 and Oman. 8 The proposed model consisted of a list of MVs reflecting the respective LV. 58 Based on a recent systematic review, all these MVs significantly affect LE.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The theoretical model proposed for this study was based on a conceptual framework from previous studies in ASEAN countries 35–37 and Oman. 8 The proposed model consisted of a list of MVs reflecting the respective LV. 58 Based on a recent systematic review, all these MVs significantly affect LE.…”
Section: Methodsmentioning
confidence: 99%
“…CB-SEM is involved in the confirmatory approach by determining how well a proposed model can estimate the covariance matrix from the dataset. As with previous studies related to LE, research had been conducted in ASEAN countries 35–37 and Oman 8 using CB-SEM. PLS-SEM is an exploratory approach to explaining the variance in the MVs within the proposed model.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a data cleaning procedure was undertaken and is considered one of the steps conducted to ensure the data's quality. Principally, imputation procedures will only be attempted on the missing random explanatory variables [45]. Furthermore, any item in this study that was found to have 20% missing data or more will be excluded and is considered ineligible to be entered into the analysis procedure entirely.…”
Section: Data Resources Data Collection and Sample Sizementioning
confidence: 99%
“…The proposed conceptual model was developed based on previous studies [44][45][46][47] and the results from a systematic review [29]. Overall, this study intends to examine the effect of multiple explanatory variables on IMR in Oman using structural equation modeling (SEM).…”
Section: The Proposed Conceptual Modelmentioning
confidence: 99%